Internalised stigma in people with rheumatoid arthritis: a cross sectional study to establish the psychometric properties of the ISMI-RA. Issue 1 (December 2016) - Corker, Elizabeth; Henderson, R.; Lempp, Heidi; Brown, June
Abstract Background Internalised stigma is theorized to be the internalisation and legitimisation of stereotypes of the diagnosis held in society and has not been quantified within patients with Rheumatoid Arthritis. This study aimed to: validate a modified version of a measure of internalised stigma, (the Internalised Stigma of Mental Illness scale, ISMI) for use in a group of patients diagnosed with rheumatoid arthritis; establish the consistency of the construct being measured, and to explore the levels of internalised stigma within this group. Methods A cross-sectional survey was conducted in London, UK with participants receiving out-patient treatment for Rheumatoid Arthritis. Participants completed the ISMI-Rheumatoid Arthritis (ISMI-RA) and a measure of self-esteem. Results One hundred respondents were interviewed by phone. The ISMI-RA was found to be reliable using a measure of internal consistency (α = 0.85) showed concurrent validity with the Index of Self Esteem (r = 0.58, p < 0.01) and discriminant validity with no association with gender (t = 1.43, p = 0.61). A quarter of respondents reported internalised stigma to a 'severe' level. Acceptability and feasibility were established. A confirmatory factor analysis provided some support for the model of internalised stigma. Conclusions The application of the ISMI-RA among the Rheumatoid Arthritis population looks promising. Internalised stigma was found to be present within this group. More research is needed to generalize these results and to explore the effects of internalised stigma on treatment adherence and quality of life.